Faktor-Faktor Yang Mempengaruhi Pergantian Auditor: - Juriati Juriati; Charoline Cheisviyanny; Mayar Afriyenti (Universitas Negeri Padang, 2019)
This research aims to determine the influence of audit quality, change in audit fees, change in management, financial distress and client size on auditor switch. This type of research is causative research. The population and sample in this research are companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2017. The sample selection in this research used a purposive sampling method. Data type is secondary data. Data collection is done by collecting documentation data of financial statements of companies listed on the Stock Exchange for the 2014-2017. The data analysis method used is logistic regression analysis, with auditor switching as the dependent variable and audit quality, change in audit fees, change in management, financial distress and client size as independent variables. The results of the research concluded that audit quality, change in audit fees, financial distress and client size have significant relationship with auditor switchi while management change does not have a significant relationship with auditor switch. The next researcher can consider using other variables such as share growth, company growth, audit tenure, audit delay and other variables that might influence auditor switch